Passivizability of Idioms: Has the Wrong Tree Been Barked Up?. (June 2020) - Kyriacou, Marianna; Conklin, Kathy; Thompson, Dominic
A growing number of studies support the partial compositionality of idiomatic phrases, while idioms are thought to vary in their syntactic flexibility. Some idioms, like kick the bucket, have been classified as inflexible and incapable of being passivized without losing their figurative interpretation (i.e., the bucket was kicked ≠ died ). Crucially, this has never been substantiated by empirical findings. In the current study, we used eye-tracking to examine whether the passive forms of (flexible and inflexible) idioms retain or lose their figurative meaning. Active and passivized idioms ( he kicked the bucket/the bucket was kicked ) and incongruous active and passive control phrases (he kicked the apple/the apple was kicked ) were inserted in sentences biasing the figurative meaning of the respective idiom ( die ). Active idioms served as a baseline. We hypothesized that if passivized idioms retain their figurative meaning ( the bucket was kicked = died ), they should be processed more efficiently than the control phrases, since their figurative meaning would be congruous in the context. If, on the other hand, passivized idioms lose their figurative interpretation ( the bucket was kicked = the pail was kicked ), then their meaning should be just as incongruous as that of both control phrases, in which case we would expect no difference in their processing. Eye movement patterns demonstrated a processing advantage for passivized idioms (flexible and inflexible) over control phrases, thus indicating that their figurative meaning was not compromised. These findings challenge classifications of idiom flexibility and highlight the creative nature of language.